THE TOOLS OF QUALITATIVE APPROACH TO MEASURE RURAL TRANSFORMATION: THE CASE OF YOGYAKARTA RURAL VILLAGE - Anna Pudianti; Atiek Suprapti; Joesron Ali Syahbana (Diponegoro University, 2019)
Yogyakarta is one of the rapidly growing Indonesian cities with its strong culture to construct a distinctive transformation, especially in the rural area. The process of transformation in rural areas is a continuous process as a form of the desire to grow. The agricultural based rural area diversify into activities other than agriculture, such as small craft industry and rural tourism. This study aims to explore tools to measure the level of transformation with a qualitative approach. The uniqueness of the transformation process in the rural area of Yogyakarta inspires the preparation of transformation measurement tools with a qualitative approach by using eight indicators to produce a depth of findings. The tools are developed by using a quadrant model of the combination of potential resources with the efforts made by the occupants. Since the case study research is being used to for the analysis, the quantitative approach could be also used to validate the result of the tools. The quantitative data is taken from secondary data of satellite imagery, government institution, and field survey. Furthermore, this research provides interesting findings by its comparative study between qualitative and quantitative approach. The qualitative approach can become a tool for explaining the dynamics of the transformation of rural area as a whole, complementing quantitative results.